2018
DOI: 10.1111/eci.12936
|View full text |Cite
|
Sign up to set email alerts
|

First‐year GFR slope and long‐term renal outcome in IgA nephropathy

Abstract: First-year GFR slope was associated with increased risk of renal progression, independent of proteinuria and histologic findings. Further studies are needed to investigate whether early GFR change can identify high-risk patients who benefit from immunosuppressive treatment in IgAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Whilst the more rapid decliners were more likely to require RRT, this did not translate into increased mortality. A previous study calculated eGFR slopes for the first-year post diagnosis of IgAN, and suggested that rapid and slow decliners over this period had significantly increased risk of progression compared to non-decliners (relative risk 8.8 and 10.2 respectively) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the more rapid decliners were more likely to require RRT, this did not translate into increased mortality. A previous study calculated eGFR slopes for the first-year post diagnosis of IgAN, and suggested that rapid and slow decliners over this period had significantly increased risk of progression compared to non-decliners (relative risk 8.8 and 10.2 respectively) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…increased risk of progression compared to non-decliners (relative risk 8.8 and 10.2 respectively) [15].…”
Section: Plos Onementioning
confidence: 99%
“…iga nephropathy is the most important factor that leads to end-stage kidney disease progression (1). it is well known that iga nephropathy is a progressive disease.…”
Section: Introductionmentioning
confidence: 99%